A permanent magnet system for Kibble balances. (11th September 2017) - Li, Shisong; Bielsa, Franck; Stock, Michael; Kiss, Adrien; Fang, Hao
Abstract: The magnet is one of the fundamental elements in Kibble balances. The Kibble balance group at the Bureau International des Poids et Mesures (BIPM) proposed a permanent magnet with a radial field, which has been widely employed in other Kibble balance experiments. In this paper, we discuss a different method of operation for the BIPM-type magnet, i.e. only the lower half of the magnetic circuit is closed. The merit of such a magnet is its convenience for opening the air gap and adjusting the coil. A disadvantage is that it can yield a lower and sloped magnetic field profile with less shielding. In the approach described, high permeability yokes are used to flatten the magnetic profile, which has proven to be a novel and convenient approach for removing the nonuniformity of the magnetic profile due to magnet magnetization asymmetries. The performance of the half-closed BIPM magnet is evaluated using experimental measurements. The results show that the half-closed magnetic circuit retains most of the main features of the fully-closed magnet and is a good option for the early stages of Kibble balance operations. In addition, the profile change due to the coil current is predicted and experimentally verified with a bifilar coil. Related systematic effects are discussed for the Planck constant measurement.